Towards elimination of HIV transmission, AIDS and HIV‐related deaths in the UK. Issue 8 (20th June 2018) - Brown, AE; Nash, S; Connor, N; Kirwan, PD; Ogaz, D; Croxford, S; De Angelis, D; Delpech, VC
Abstract : Objectives: Our objective was to present recent trends in the UK HIV epidemic (2007–2016) and the public health response. Methods: HIV diagnoses and clinical markers were extracted from the HIV and AIDS Reporting System; HIV testing data in sexual health services (SHS) were taken from GUMCAD STI Surveillance System. HIV data were modelled to estimate the incidence in men who have sex with men (MSM) and post‐migration HIV acquisition in heterosexuals. Office for National Statistics (ONS) data enabled mortality rates to be calculated. Results: New HIV diagnoses have declined in heterosexuals as a result of decreasing numbers of migrants from high HIV prevalence countries entering the UK. Among MSM, the number of HIV diagnoses fell from 3570 in 2015 to 2810 in 2016 (and from 1554 to 1096 in London). Preceding the decline in HIV diagnoses, modelled estimates indicate that transmission began to fall in 2012, from 2800 [credible interval (CrI) 2300–3200] to 1700 (CrI 900–2700) in 2016. The crude mortality rate among people promptly diagnosed with HIV infection was comparable to that in the general population (1.22 vs . 1.39 per 1000 aged 15–59 years, respectively). The number of MSM tested for HIV at SHS increased annually; 28% of MSM who were tested in 2016 had been tested in the preceding year. In 2016, 76% of people started antiretroviral therapy within 90 days of diagnosis (33% in 2007). Conclusions: The dual successes of the HIV transmission decline in MSM and reduced mortality are attributable to frequent HIV testing and prompt treatment (combination prevention). Progress towards the elimination of HIV transmission, AIDS and HIV‐related deaths could be achieved if combination prevention, including pre‐exposure prophylaxis, is replicated for all populations.